Disaster as Opportunity? Cyclone Pam and the Transmission of Cultural Heritage. Issue 1 (2nd April 2020) - Ballard, Chris; Wilson, Meredith; Nojima, Yoko; Matanik, Richard; Shing, Richard
ABSTRACT: Culture, by its very nature, is always at risk of change – whether through transformation, destruction or redefinition. So how might culture be said to be particularly at risk in the context of 'natural' disasters, and how are disasters 'naturalised' or incorporated under the terms of different cultural regimes? An earlier focus on the impacts to built or tangible heritage is increasingly being balanced by a concern for the transformations wrought by disasters in the intangible heritage of communities. Through the recent event of Cyclone Pam in 2015, and a case study of the World Heritage site of Chief Roi Mata's Domain (CRMD), we explore the ways in which repetitive natural hazards have shaped culture and tangible and intangible forms of heritage in Vanuatu. We focus in particular on the issue of cultural transmission at CRMD and its relationship to natural hazards through the device of a 'disaster biography'. Risk can also carry with it the prospect of opportunity, and our paper seeks to understand how opportunity might be present in post-disaster reworkings of culture and heritage.